IJCM_307A: Perception and practice of Nipah among first year undergraduate medical students of knct medical college - Razak Hafna M; Jayakrishnan T; Manju T. L; Mohandas Bindu; Laxman Anjali; Krishna Sruthi P (Wolters Kluwer Medknow Publications, 2024)
Background: Nipah infection is a zoonotic disease caused by Nipah virus with a very high case fatality rate (40-75%). The current outbreak (12-15 September 2023) was the third Nipah virus outbreak in Kozhikode district of Kerala, and overall the fourth outbreak in Kerala state since 2018. The state government had declared containment zones in the district and there was restriction of movement, public gatherings; wearing of masks and social distancing was mandatory in public spaces. The educational institutions including professional colleges were closed as a precautionary measure and switched to online classes. In this context, this study was conducted among the first-year medical students of KMCT medical college Objective: To assess the Perception and Practice about Nipah among first year undergraduate medical students of KMCT medical college Methodology: A cross sectional study was done among 2023 batch students of KMCT medical college students from September 18th to October 28, 2023. All the 150 students were taken by universal sampling for the study, out of which 144 were present at the time of data collection. Data was collected by investigators using a semi-structured questionnaire consisting of knowledge, attitude and practice-based sections. Scoring was done. The data was analyzed and recorded as frequencies and percentage. Results: Majority of the students (69%) had poor knowledge on Nipah, 29% had satisfactory knowledge and 2% of the students had very good knowledge. Majority of the students (89%) had good attitude towards Nipah while 10% had poor attitude. 68% students were found to have followed excellent practices, 30% had followed satisfactory practices while 2% had not practiced any good etiquette needed during an outbreak. Conclusion: Though they were having poor knowledge about Nipah, they followed good practices that helped in preventing and controlling the disease.